Associativismo negro e práticas culturais: ações coletivas no reconhecimento do Quilombo Urbano Liberdade/MA - VALE , Ana Talycia Marques (2024)
The work presented analyzes the characteristics of cultural practices in the urban quilombo Liberdade to understand the recognition of the territory that occurred in 2019, as the first urban quilombo in Maranhão and the largest in Latin America. It sought to investigate how the articulations of narratives occur in order to reveal how the different contours of relationships are part of the cultural memory of the Liberdade neighborhood in the construction of quilombola identity in the urban area, in which it has been constructed by different groups with different forms of contribution. This research examines how forms of black associations also occur through the agency of black women in maintaining tradition. The research takes place through the thinking of critical social theory, the research data were collected through interviews, where dialogically through orality we examined the aspect of collective and individual memory of th827788e residents, we carried out observations and records as well as the analysis of images of the cultural manifestations present in the neighborhood, where in this perspective other methodological forms of observation in the field of human and social sciences are intended. Through the research, it was possible to realize that the new forms of black associations are approved by the concept of self-definition regarding being a quilombola in urban space, as well as other forms of recognition, both in its territorial and documentary aspect of the space.